E-Cigarette Dependence and Weight-Related Attitudes/Behaviors Associated With Eating Disorders in Adolescent Girls - Naveed, Aamina; Dang, Nhan; Gonzalez, Pierina; Choi, So Hee; Mathew, Amanda; Wardle, Margaret; Garey, Lorra; Hamidovic, Ajna (Frontiers in Psychiatry, 2021)
Background: Although numerous motivations for vaping have been identified in adolescents, no study to date examined a possible link between vaping and attitudes/behaviors that are associated with eating disorders in adolescent females. Examining this question in adolescent females is especially relevant given the higher prevalence of eating disorders in women. Methods: The present study recruited 299 girls (between 13 to 17 years old) via Facebook advertisement to complete a REDCap survey, which included Electronic Cigarette Dependence Index (ECDI), Minnesota Eating Behavior Survey (MEBS), and demographic questions. Data were analyzed using nonparametric Spearman rank correlation test in R. Results: Electronic Cigarette Dependence Index (ECDI) scores were correlated with three out of four subscales of MEBS: weight preoccupation (WP), binge eating (BE) and compensatory behavior (CB), with the following results for Spearman correlation tests: (1) WP: rho =0.13, p=0.02, S = 3853727; (2) BD: rho=0.06, p=0.28, S = 4175196; (3) BE: rho=0.15, p=0.0095, S = 3787501; (4) CB: rho=0.021, p= 0.00027; S = 3523183. Conclusion: The present study adds to the current literature examining motivations for e-cigarette use in adolescent girls. As eating disorders and e-cigarette dependence are significant public health concerns, our results highlight the need for intervention development.